PENGARUH PENYULUHAN DENGAN MEDIA ANIMASI TERHADAP PENINGKATAN PENGETAHUAN ORANG TUA TENTANG TOPIKAL APLIKASI FLUOR - Juliana, Delvi; Praptiwi, Yenni Hendriani; Chaerudin, Denden Ridwan (Poltekkes Kemenkes Bandung, 2025)
The prevalence of dental caries in Indonesia is estimated to be 80%. In children aged between six and 11 years, dental caries is a chronic condition that is prevalent and relatively high. Nevertheless, some measures can be taken, such as the application of topical fluoride. Nevertheless, a considerable number of parents remain unaware of the topical application of fluoride. The objective of this study was to determine the impact of an educational animation on parental knowledge about topical fluoride applications. The study employed a pre-experimental design with a one-group, pretest-post-test design. The population of this study consisted of all parents (mothers and guardians) of students at DTA Al-Fath, totalling 18 individuals. The sampling method employed was total sampling. The data were analysed using the paired sample t-test. The results of the paired sample t-test indicate that the average level of parental knowledge regarding topical fluoride applications prior to the implementation of the educational intervention was 45.83. Following the provision of instruction via the medium of animation, the level of parental awareness regarding topical applications of fluoride increased, with an average score of 86.67. The findings of this study indicate a significant impact on the level of parental awareness regarding topical fluoride applications in DTA Al-Fath, both before and after the implementation of an educational intervention utilising animated media. The statistical significance of this impact is evidenced by a p-value of 0.000, which is less than 0.05